Avaliação do potencial antitumoral in vitro dos derivados sintéticos do indol - Andrade, Ana Karolina de Souza (2021)
Cancer is considered a public health problem worldwide due to the high mortality rates. It is caused by mutations in the oncogenes that control the cell cycle and that end up generating disordered cell proliferation. The antineoplastic agents currently used for the treatment of the disease still generate many adverse effects, such as: neurotoxicity, liver and kidney damage, among others. Because of this, it is necessary to search for new compounds that may have a cytotoxic potential in tumor cells. In this context, the indole. without a compound that is widely distributed among natural products and that presents several biological activities, such as antitumor activity, which has already been investigated in indole alkaloids such as ellipticin, it becomes an important source for the development and search for new molecules that come to show antitumor activity. Thus, the objective of this work was to evaluate the antitumor activity of synthetic indole derivatives. In the first stage of the project, twelve indole compounds were selected at a concentration of 25 µg / mL to assess the degree of inhibition in tumor lines of lung cancer, melanoma and glioma by the SRB technique. According to the chemical structure and high degree of inhibition in the tumor lines, the substances NM-18-05, NM-01-38-29 and NM-01-45-33 were selected to assess cytotoxicity and calculate CI50. The CI50 results show that the NM-01-38-29 molecule was effective in promoting antitumor activity in the glioma (C6) lineage. Based on this result, C6 cells were treated with the compound NM-01-38-29 to evaluate cellular mechanisms such as the ability to form colonies, the capacity for cell migration, and the evaluation of morphological changes. The compound NM-01-38-29 was shown to be able to decrease the number of colonies as well as inhibiting the migratory capacity of C6 cells. In addition, it was possible to observe morphological changes with DAPI and FALOIDINA/FITC dyes suggesting cell death due to apoptosis in glioma cells. These results show that indole derivatives have cytotoxic action in different tumor lines and that the structural differences of these compounds led to differences in the value of the degree of inhibition found compared to the cell lines used. The NM-01-38-29 molecule showed a greater cytotoxic effect on the C6 cell line. The results of cytotoxic activity based on the degree of inhibition plus the results of cellular mechanisms show that the compound NM-01-38-29 has a promising effect for the treatment of cancer.